Association of Probiotic Treatment With Antibiotics in Male Accessory Gland Infections. Issue 5 (October 2022) - Grande, Giuseppe; Pompa, Giuseppina; Astorri, Anna Laura; Pontecorvi, Alfredo; Milardi, Domenico
Male accessory gland infection (MAGI) represents a frequent disease, commonly treated with antibiotics alone. However, in approximately 40% to 50% of patients, persistent infection is detected. Intestinal dysbiosis is involved in the pathogenesis of prostatitis. We aimed to evaluate the efficacy of antibiotic treatment in association with a specific probiotic supplementation. A total of 104 infertile patients, with microbiological analysis on semen and/or prostatic secretions positive for Gram-negative bacteria, have been enrolled. All patients received antibiotic treatment with fluoroquinolones. In total, 84 patients received a commercial association of Enterococcus faecium and Saccharomyces boulardii during antibiotic treatment, followed by treatment with Lactobacilli. After the treatment, a complete microbiological analysis was repeated. Polymicrobial infections have been observed in 11% of patients, while infections due to a single germ were reported in 89% of the patients. After the treatment was performed, a complete eradication with negative semen culture and microbiological analysis on prostatic secretion was observed in 64 of 84 patients (76.2%), while only 10 of 20 patients receiving antibiotics alone (50%; p < .05) reported negative microbiological analysis. Persistent infections have been observed only in patients with infections due to Enterococcus faecalis and Escherichia coli . This study represents the first approach demonstrating the efficacy of a specific probiotic treatment in reducing the rate of persistent infections in patients with MAGI.